Correlation between Basic Life Support Knowledge Level and Motivation to Help Cardiac Arrest Victims - Dewi, Ni Nyoman Ari Kundari; Agus Baratha Suyasa; Luh Gde Nita Sri Wahyuningsih (Jurnal EduHealth, 2022)
Basic Life Assistance (BHD) is very important to know by the general public, especially health students because emergency events can be found anywhere and anytime, so they can be a provision to help victims of cardiac arrest.Cardiac Arrest or cardiac arrest is one of the most dangerous and deadly diseases in the world.Cardiac arrest occurs when the heart's electrical system malfunctions. Basic life support measures carried out by people around the sufferer immediately after the incident can increase the patient's survival rate. The purpose of this study was to determine the relationship between the level of basic life support knowledge and the motivation to help victims of cardiac arrest. This study uses a correlational analytic approach with a cross sectional approach. The sample in this study was 101 respondents who were taken by total sampling technique. Data was collected using a questionnaire and analyzed by statistical inferential. The results showed that there was a significant relationship between knowledge of basic life support and motivation to help victims of cardiac arrest in respondents where the p-value was <0.